1996
DOI: 10.1007/bf00023895
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of broad spectrum resistance to potyviruses using doubled haploid lines of pepper (Capsicum annuum L.)

Abstract: Genetic analysis of resistance to PVY in androgenetic doubled haploid lines, Fl, F2 and backcross progenies of the Mexican pepper line, CM 334 (Capsicum annuum L.), was performed . Three reaction types were observed when seedlings were inoculated with several PVY strains of different pathotypes and with an American PeMV strain . Resistant genotypes never showed systemic symptoms although some individuals sporadically developed necrotic local lesions on inoculated cotyledons . Susceptible genotypes exhibited ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 21 publications
(17 reference statements)
4
42
1
4
Order By: Relevance
“…The data presented in Table 1 suggest that the resistance carried by the variety 'SCM-334' against the PVY pathotype 1-2 is due to a unique and dominant gene described as Pvr4 (Dogimont et al 1996).…”
Section: Inoculation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in Table 1 suggest that the resistance carried by the variety 'SCM-334' against the PVY pathotype 1-2 is due to a unique and dominant gene described as Pvr4 (Dogimont et al 1996).…”
Section: Inoculation Resultsmentioning
confidence: 99%
“…Subsequently, some oligogenic resistances were also reported (Nagai and Costa 1972). Later, a monogenic dominant gene named Pvr4, that confers resistance against all known PVY pathotypes and pepper mottle virus (PepMoV), was found in the Capsicum annuum L. line 'Serrano Criollo de Morelos-334' (SCM-334) (Pasko et al 1992;Dogimont et al 1996). Recently, a new dominant source of resistance, Pvr7, has been described in Capsicum chinense Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these resistances are oligogenic or polygenic (Caranta & Palloix, 1996) and two monogenic and dominant resistances have also been reported (Dogimont et al, 1996;Grube et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Dogimont et al (1996) reported that cultivars Vat and CM334 contain the lethal systemic necrosis factor Pn1. When inoculated with Potato virus Y (PVY) P(0) and PVY (1,2), Vat developed lethal necrosis, whereas CM334 developed the typical hypersensitive-response type of resistance.…”
Section: Introductionmentioning
confidence: 99%